Sustainability of Higher Education: The Role Of Financial Transparency, Continuing Education And Job Satisfaction - Rudiyanto Rudiyanto; Nuzulul Hidayati; Zakiyya Tunnufus (Universitas Muhammadiyah Malang, 2022)
Our article focuses on the problem of job satisfaction and loyalty of permanent lecturers in accounting at private universities. This article aims to provide empirical evidence regarding: the relationship between financial transparency, continuing education, and job satisfaction on the loyalty of accounting lecturers at private universities. We were collected data using a questionnaire that distributed directly to 279 accounting lecturers, from 12 universities in Indonesia as a sample. Structural Equation Modeling (SEM) analysis was employed to investigate the form of construct reliability. After the construct of each variable was declared reliable, we analyzed the data based on the level of relationship and influence of each variable. Our results showed that transparency in financial, continuing education, and job satisfaction can increase the loyalty of accounting lecturers. Our findings are expected to contribute to higher education leaders in taking long-term strategic policies through increasing financial management transparency, and continuing education. Through the level of lecturer satisfaction will trigger loyalty as a force in achieving the vision and mission of the university.